aboutsummaryrefslogtreecommitdiffstats
path: root/buch/papers/kugel/proofs.tex
blob: c3d4f01f56bea3745e232cf3cea0ae5d1fa9e889 (plain)
1
2
3
4
5
6
7
8
9
10
11
12
13
14
15
16
17
18
19
20
21
22
23
24
25
26
27
28
29
30
31
32
33
34
35
36
37
38
39
40
41
42
43
44
45
46
47
48
49
50
51
52
53
54
55
56
57
58
59
60
61
62
63
64
65
66
67
68
69
70
71
72
73
74
75
76
77
78
79
80
81
82
83
84
85
86
87
88
89
90
91
92
93
94
95
96
97
98
99
100
101
102
103
104
105
106
107
108
109
110
111
112
113
114
115
116
117
118
119
120
121
122
123
124
125
126
127
128
129
130
131
132
133
134
135
136
137
138
139
140
141
142
143
144
145
146
147
148
149
150
151
152
153
154
155
156
157
158
159
160
161
162
163
164
165
166
167
168
169
170
171
172
173
174
175
176
177
178
179
180
181
182
183
184
185
186
187
188
189
190
191
192
193
194
195
196
197
198
199
200
201
202
203
204
205
206
207
208
209
210
211
212
213
214
215
216
217
218
219
220
221
222
223
224
225
226
227
228
229
230
231
232
233
234
235
236
237
238
239
240
241
242
243
244
245
246
247
248
249
250
251
252
253
254
255
256
257
258
259
260
261
262
263
264
265
266
267
268
269
270
271
272
273
274
275
276
277
278
279
280
281
282
283
284
285
286
% vim:ts=2 sw=2 et spell tw=80:
\section{Long Proofs}

Here, we will give the long and tedious proofs we skipped earlier.

\subsection{Legendre Polynomials} \label{kugel:sec:proofs:legendre}

\begin{proof}[Proof of lemma \ref{kugel:thm:legendre-poly}]
  It was stated that the polynomial function
  \begin{equation*}
    P_n(z) = \sum^{\lfloor n/2 \rfloor}_{k=0}
      \frac{(-1)^k}{2^n s^k!} \frac{(2n - 2k)!}{(n - k)! (n-2k)!} z^{n - 2k}
  \end{equation*}
  is the only finite solution of the Legendre equation
  \begin{equation}
    \label{kugel:eqn:legendre-bis}
    (1 - z^2)\frac{d^2 Z}{dz^2}
    - 2z\frac{d Z}{dz}
    + n(n + 1) Z(z) = 0,
  \end{equation}
  when $n \in \mathbb{Z}$ and $z \in [-1; 1]$. In order to prove this fact, we
  begin with the power series \emph{Ansatz}
  \begin{equation*}
    Z(x) = \sum_{k=0}^\infty a_k z^k,
    \quad\text{from which follows that}\quad
    \frac{dZ}{dz} = \sum_{k=0}^\infty k a_k z^{k-1}, \qquad
    \frac{d^2 Z}{dz^2} = \sum_{k=0}^\infty k (k-1) a_k z^{k-2}.
  \end{equation*}
  Since the power series method converges only up to the nearest singularity,
  which is at $z=1$ (and $z=-1$), we shall remark that we will find a solution
  only for $|z|<1$. The Legendre equation \eqref{kugel:eqn:legendre-bis} can be
  therefore rewritten as
  \begin{align}
    0 &= (1-z^2) \sum_{k=0}^\infty k (k-1) a_k z^{k-2}
      - 2z\sum_{k=0}^\infty k a_k z^{k-1}
      + n(n+1)\sum_{k=0}^\infty a_k z^k \nonumber \\
    &= \sum_{k=0}^\infty k (k-1) a_k z^{k-2}
      - \sum_{k=0}^\infty k (k-1) a_k z^{k}
      - 2z\sum_{k=0}^\infty k a_k z^{k-1}
      + n(n+1)\sum_{k=0}^\infty a_k z^k. \label{kugel:eqn:legendre-ansatz}
  \end{align}
  Considers that by shifting the index $k$ in the sum of first term
  \begin{equation*}
    \sum_{k=0}^\infty k (k-1) a_k z^{k-2}
    = \sum_{k=-2}^\infty (k+2)(k+1) a_{k+2} z^k
    = \sum_{k=0}^\infty (k+2)(k+1) a_k z^k,
  \end{equation*}
  since when $k = -1$ or $-2$ the summand is zero. This means that
  \eqref{kugel:eqn:legendre-ansatz} becomes
  \begin{align*}
    \sum_{k=0}^\infty &(k+1)(k+2) a_{k+2} z^{k}
      - \sum_{k=0}^\infty k (k-1) a_k z^{k}
      - 2\sum_{k=0}^\infty k a_k z^k
      + n(n+1)\sum_{k=0}^\infty a_k z^k \nonumber \\
    &= \sum_{k=0}^\infty \big[
      (k+1)(k+2) a_{k+2}
      - k (k-1) a_k
      - 2 k a_k
      + n(n+1) a_k
    \big] z^k \stackrel{!}{=} 0,
  \end{align*}
  which is equivalent to saying that
  \begin{equation*}
    (k+1)(k+2) a_{k+2} - k (k-1) a_k - 2 k a_k + n(n+1) a_k = 0,
  \end{equation*}
  so we can derive a recurrence relation for $a_{k+2}$:
  \begin{equation}
    \label{kugel:eqn:coeff-recursion}
    a_{k+2} = \frac{k (k-1) - 2 k + n(n+1)}{(k+1)(k+2)}a_k
    = \frac{(k-n)(k+n+1)}{(k+2)(k+1)}a_k.
  \end{equation}
  Following the relation \eqref{kugel:eqn:coeff-recursion}, if we want to
  compute $a_6$ we would have
  \begin{align*}
    a_{6} = -\frac{(n-4)(n+5)}{6\cdot 5} a_4
      &= \left( -\frac{(n-4)(5+n)}{6 \cdot 5} \right)
         \left( -\frac{(n-2)(n+3)}{4 \cdot 3} \right) a_2 \\
      &= \left( -\frac{(n-4)(n+5)}{6 \cdot 5} \right)
         \left( -\frac{(n-2)(n+3)}{4 \cdot 3} \right)
         \left( -\frac{n(n+1)}{2 \cdot 1} \right)  a_0 \\
      &= -\frac{(n+5)(n+3)(n+1)n(n-2)(n-4)}{6!} a_0.
  \end{align*}
  One can generalize this relation for the $i^\text{th}$ even ($i = 2k$)
  coefficient and obtain
  \begin{equation*}
    a_{2k} = (-1)^k \frac{(n+(2k-1))(n+(2k-1)-2)
      \hdots (n-(2k-2)+2)(n-(2k-2))}{(2k)!}a_0,
  \end{equation*}
  and a similar expression can also be written for the odd coefficients
  $a_{2k-1}$. In the latter case, the equation starts from $a_1$ and to find the
  pattern we can write the recursion for an odd coefficient, for example for
  $a_7$:
  \begin{align*}
    a_{7} = -\frac{(n-5)(n+6)}{7\cdot 6} a_5
      &= \left( -\frac{(n-5)(n+6)}{7 \cdot 6} \right)
         \left( -\frac{(n-3)(n+4)}{5 \cdot 4} \right) a_3 \\
      &= \left( -\frac{(n-5)(n+6)}{7 \cdot 6} \right)
         \left( -\frac{(n-3)(n+4)}{5 \cdot 4} \right)
         \left( -\frac{(n-1)(n+2)}{3 \cdot 2} \right) a_1 \\
      &= -\frac{(n+6)(n+4)(n+2)(n-1)(n-3)(n-5)}{7!} a_1.
  \end{align*}
  As before, we can generalize this equation for the $i^\text{th}$ odd ($i =
  2k+1$) coefficient and get
  \begin{equation*}
    a_{2k+1} = (-1)^k \frac{(n + 2k)(n+2k-2)
      \hdots (n-(2k-1)+2)(n-(2k-1))}{(2k+1)!} a_1.
  \end{equation*}
  Now, if we let
  \begin{align*}
    Z_\text{e}^K(z) &:=
      \sum_{k=0}^K(-1)^k \frac{
        (n+(2k-1))(n+(2k-1)-2) \hdots
        \color{red}(n-(2k-2)+2)(n-(2k-2))
      }{(2k)!} z^{2k}, \\
    Z_\text{o}^K(z) &:=
      \sum_{k=0}^K(-1)^k \frac{
        (n + 2k)(n+2k-2)\hdots \color{blue} (n-(2k-1)+2)(n-(2k-1))
      }{(2k+1)!} z^{2k+1},
  \end{align*}
  the solution to the Legendre equation \eqref{kugel:eqn:legendre-bis} can be
  written as
  \begin{equation}\label{eq:solution}
    Z(z) = \lim_{K \to \infty} \left[
      a_0 Z_\text{e}^K(z) + a_1 Z_\text{o}^K(z)
    \right].
  \end{equation}

  The colored parts can be analyzed separately:
  \begin{itemize}
    \item[\textcolor{red}{\textbullet}] Suppose that $n=n_0$ is an even number. Then the red part, for a specific value of $k=k_0$, will follow the following relation:
      \begin{equation*}
        n_0-(2k_0-2)=0. 
      \end{equation*}
      From that point on, given the recursive nature of Eq.\eqref{eq:recursion}, all the subsequent coefficients will also be 0, making the sum finite.
      \begin{equation*}
        a_{2k}=0 \iff y_{\text{o}}^{2k}(x)=y_{\text{o}}^{2k_0}(x), \quad \forall k>k_0
      \end{equation*} 
    \item[\textcolor{blue}{\textbullet}] Suppose that $n=n_0$ is an odd number. Then the blue part, for a specific value of $k=k_0$, will follow the following relation 
      \begin{equation*}
        n_0-(2k_0-1)=0.  
      \end{equation*}
      From that point on, for the same reason as before, all the subsequent coefficients will also be 0, making the sum finite.
      \begin{equation*}
        a_{2k+1}=0 \iff y_{\text{o}}^{2k+1}(x)=y_{\text{o}}^{2k_0+1}(x), \quad \forall k>k_0
      \end{equation*}
  \end{itemize} 

  There is the possibility of expressing the solution in Eq.\eqref{eq:solution} in a more compact form, combining the two solutions $y_\text{o}^K(x)$ and $y_\text{e}^K(x)$. They are both a polynomial of maximum degree $n$, assuming $n \in \mathbb{N}$. In the case where $n$ is even, the polynomial solution
  \begin{equation*}
    \lim_{K\to \infty} y_\text{e}^K(x)
  \end{equation*}
  will be a finite sum. If instead $n$ is odd, will be 
  \begin{equation*}
    \lim_{K\to \infty} y_\text{o}^K(x)
  \end{equation*}
  to be a finite sum. 

  Depending on the coefficient we start with, $a_1$ or $a_0$, we will obtain the odd or even polynomial respectively. Starting with the last coefficient $a_n$ and, recursively, calculating all the others in descending order, we can express the two parts $y_\text{o}^K(x)$ and $y_\text{e}^K(x)$ with a single sum. Hence, because we start with the last coefficient, the choice concerning $a_1$ and $a_0$ will be at the end of the sum, and not at the beginning. To compact Eq.\eqref{eq:solution}, Eq.\eqref{eq:recursion} can be reconsidered to calculate the coefficient $a_{k-2}$, using $a_k$
  \begin{equation*}
    a_{k-2} = -\frac{(k+2)(k+1)}{(k-n)(k+n+1)}a_k
  \end{equation*}
  Now the game is to find a pattern, as before. Remember that $n$ is a fixed parameter of Eq.\eqref{eq:legendre}.  
  \begin{align*}
    a_{n-2} &= -\frac{n(n-1)}{2(2n-1)}a_n, \\
    a_{n-4} &= -\frac{(n-2)(n-3)}{4(2n-3)}a_{n-2} \\
    &= -\frac{(n-2)(n-3)}{4(2n-3)}-\frac{n(n-1)}{2(2n-1)}a_n.
  \end{align*}
  In general 
  \begin{equation}\label{eq:general_recursion}
    a_{n-2k} = (-1)^k \frac{n(n-1)(n-2)(n-3) \hdots (n-2k+1)}{2\cdot4\hdots 2k(2n-1)(2n-3)\hdots(2n-2k+1)}a_n
  \end{equation}
  The whole solution can now be written as
  \begin{align}
    y(x) &= a_n x^n + a_{n-2} x^{n-2} + a_{n-4} x^{n-4} + a_{n-6} x^{n-6} + \hdots + \begin{cases} 
      a_1 x, \quad &\text{if } n \text{ odd} \\ 
      a_0, \quad  &\text{if } n \text{ even} 
    \end{cases} \nonumber \\
    &= \sum_{k=0}^{\lfloor \frac{n}{2} \rfloor} a_{n-2k}x^{n-2k} \label{eq:solution_2}
  \end{align}
  By considering
  \begin{align}
    (2n-1)(2n-3)\hdots (2n-2k+1)&=\frac{2n(2n-1)(2n-2)(2n-3)\hdots(2n-2k+1)}
    {2n(2n-2)(2n-4)(2n-6)\hdots(2n-2k+2)} \nonumber \\ 
    &=\frac{\frac{(2n)!}{(2n-2k)!}}
    {2^kn(n-1)(n-2)(n-3)\hdots(n-k+1)} \nonumber \\
    &=\frac{\frac{(2n)!}{(2n-2k)!}}
    {2^k\frac{n!}{(n-k)!}}=\frac{(n-k)!(2n)!}{n!(2n-2k)!2^k} \label{eq:1_sub_recursion}, \\
    2 \cdot 4  \hdots 2k &= 2^r 1\cdot2 \hdots r = 2^r r!\label{eq:2_sub_recursion}, \\
    n(n-1)(n-2)(n-3) \hdots (n-2k+1) &= \frac{n!}{(n-2k)!}\label{eq:3_sub_recursion}.
  \end{align}
  Eq.\eqref{eq:solution_2} can be rewritten as
  \begin{equation}\label{eq:solution_3}
    y(x)=a_n \sum_{k=0}^{\lfloor \frac{n}{2} \rfloor} (-1)^k \frac{n!^2(2n-2k)!}{k!(n-2k)!(n-k)!(2n)!}  x^{n-2k}.
  \end{equation}
  Eq.\eqref{eq:solution_3} is defined for any $a_n$. By letting $a_n$ be declared as
  \begin{equation*}
    a_{n} := \frac{(2n)!}{2^n n!^2},
  \end{equation*}
  the so called \emph{Legendre polynomial} emerges
  \begin{equation}\label{eq:leg_poly}
    P_n(x):=\sum_{k=0}^{\lfloor \frac{n}{2} \rfloor} (-1)^k \frac{(2n-2k)!}{2^n k! (n-k)!(n-2k)!} x^{n-2k} 
  \end{equation}
\end{proof}

\subsection{Associated Legendre Equation}
\label{kugel:sec:proofs:associated-legendre}

\begin{lemma}\label{kugel:lemma:sol_associated_leg_eq}
  If $Z_n(z)$ is a solution of the Legendre equation \eqref{kugel:eqn:legendre},
  then
  \begin{equation*}
    P^m_n(z) = (1 - z^2)^{m/2} \frac{d^m}{dz^m}Z_n(z)
  \end{equation*}
  solves the associated Legendre equation \eqref{kugel:eqn:associated-legendre}.
\end{lemma}
% \begin{proof} [TODO: modificare la $m$ (è già usata come costante di separazione) o forse è giusta (?)]
\begin{proof}
    To begin, we can start by differentiating $m$ times Eq.\eqref{kugel:eq:leg_eq} (which is staisfied by $y(x)$), obtaining
    \begin{equation}\label{eq:lagrange_mderiv}
    \frac{d^m}{dx^m}\left[ (1-x^2)\frac{d^2y}{dx^2} \right] -2 \frac{d^m}{dx^m}\left[ x\frac{dy}{dx} \right] + n(n+1)\frac{d^m}{dx^m}y=0.
    \end{equation}
    \emph{Leibniz's theorem} says, that if we want to differentiate $m$ times a multiplication of two functions, we can use the binomial coefficients to build up a sum. This allows us to be more compact, obtaining 
    \begin{equation}\label{eq:leibniz}
    \frac{d^m}{dx^m}[u(x)v(x)] = \sum_{i=0}^m \binom{n}{i} \frac{d^{m-i}u}{dx^{m-1}} \frac{d^{i}v}{dx^i}.
    \end{equation}
    Using Eq.\eqref{eq:leibniz} in Eq.\eqref{eq:lagrange_mderiv}, we have
    \begin{align}
    (1-x^2)\frac{d^{m+2}y}{dx^{m+2}} &+ m \frac{d}{dx}(1-x^2)\frac{d^{m+1}y}{dx^{m+1}} + \frac{m(m-1)}{2}\frac{d^{2}}{dx^{2}}(1-x^2)\frac{d^{m}y}{dx^{m}} + n(n+1)\frac{d^m{}y}{dx^{m}} \nonumber \\
    &-2\left(x\frac{d^{m+1}y}{dx^{m+1}} + m\frac{d}{dx}x\frac{d^{m}y}{dx^{m}} \right) \nonumber \\
    &= (1-x^2)\frac{d^{m+2}y}{dx^{m+2}} -2x(m+1)\frac{d^{m+1}y}{dx^{m+1}}+(n(n+1)-m(m-1)-2m)\frac{d^{m}y}{dx^{m}}=0. \label{eq:aux_3}
    \end{align}
    To make the notation easier to follow, a new function can be defined
    \begin{equation*}
    \frac{d^{m}y}{dx^{m}} := y_m.
    \end{equation*}
    Eq.\eqref{eq:aux_3} now becomes
    \begin{equation}\label{eq:1st_subs}
    (1-x^2)\frac{d^{2}y_m}{dx^{2}} -2x(m+1)\frac{dy_m}{dx}+(n(n+1)-m(m+1))y_m=0
    \end{equation}
    A second function can be further defined as
    \begin{equation*}
    (1-x^2)^{\frac{m}{2}}\frac{d^{m}y}{dx^{m}} = (1-x^2)^{\frac{m}{2}}y_m := \hat{y}_m,
    \end{equation*}
    allowing to write Eq.\eqref{eq:1st_subs} as
    \begin{equation}\label{eq:2st_subs}
    (1-x^2)\frac{d^2}{dx^2}[\hat{y}_m(1-x^2)^{-\frac{m}{2}}] -2(m+1)x\frac{d}{dx}[\hat{y}_m(1-x^2)^{-\frac{m}{2}}] + (n(n+1)-m(m+1))\hat{y}_m(1-x^2)^{-\frac{m}{2}}=0.
    \end{equation}
    The goal now is to compute the two terms 
    \begin{align*}
    \frac{d^2}{dx^2}[\hat{y}_m(1-x^2)^{-\frac{m}{2}}] &=  \frac{d^2\hat{y}_m}{dx^2} (1-x^2)^{-\frac{m}{2}} + \frac{d\hat{y}_m}{dx}\frac{m}{2}(1-x^2)^{-\frac{m}{2}-1}2x \\
    &+ m\left( \frac{d\hat{y}_m}{dx} x (1-x^2)^{-\frac{m}{2}-1} + \hat{y}_m (1-x^2)^{-\frac{m}{2}-1} - \hat{y}_m x (-\frac{m}{2}-1)(1-x^2)^{-\frac{m}{2}} 2x\right) \\
    &= \frac{d^2\hat{y}_m}{dx^2} (1-x^2)^{-\frac{m}{2}} + \frac{d\hat{y}_m}{dx}mx (1-x^2)^{-\frac{m}{2}-1} + m\frac{d\hat{y}_m}{dx}x (1-x^2)^{-\frac{m}{2}-1}\\
    &+ m\hat{y}_m  (1-x^2)^{-\frac{m}{2}-1} + m\hat{y}_m x^2(m+2)(1-x^2)^{-\frac{m}{2}-2}
    \end{align*}
    and
    \begin{align*}
    \frac{d}{dx}[\hat{y}_m(1-x^2)^{-\frac{m}{2}}] &= \frac{d\hat{y}_m}{dx}(1-x^2)^{-\frac{m}{2}} + \hat{y}_m\frac{m}{2}(1-x^2)^{-\frac{m}{2}-1}2x \\
    &= \frac{d\hat{y}_m}{dx}(1-x^2)^{-\frac{m}{2}} + \hat{y}_mm(1-x^2)^{-\frac{m}{2}-1}x,
    \end{align*}
    to use them in Eq.\eqref{eq:2st_subs}, obtaining
    \begin{align*}
    (1-x^2)\biggl[\frac{d^2\hat{y}_m}{dx^2} (1-x^2)^{-\frac{m}{2}} &+ \frac{d\hat{y}_m}{dx}mx (1-x^2)^{-\frac{m}{2}-1} + m\frac{d\hat{y}_m}{dx}x (1-x^2)^{-\frac{m}{2}-1} \\ 
    &+ m\hat{y}_m  (1-x^2)^{-\frac{m}{2}-1} + m\hat{y}_m x^2(m+2)(1-x^2)^{-\frac{m}{2}-2}\biggr] \\
    &-2(m+1)x\left[  \frac{d\hat{y}_m}{dx}(1-x^2)^{-\frac{m}{2}} + \hat{y}_mm(1-x^2)^{-\frac{m}{2}-1}x \right] \\
    &+ (n(n+1)-m(m+1))\hat{y}_m(1-x^2)^{-\frac{m}{2}}=0.\\
    \end{align*}
    We can now divide by $(1-x^2)^{-\frac{m}{2}}$, obtaining
    \begin{align*}
    (1-x^2)\biggl[\frac{d^2\hat{y}_m}{dx^2} &+ \frac{d\hat{y}_m}{dx}mx (1-x^2)^{-1} + m\frac{d\hat{y}_m}{dx}x (1-x^2)^{-1} + m\hat{y}_m  (1-x^2)^{-1} + m\hat{y}_m x^2(m+2)(1-x^2)^{-2}\biggr] \\
    &-2(m+1)x\left[  \frac{d\hat{y}_m}{dx} + \hat{y}_mm(1-x^2)^{-1}x \right] + (n(n+1)-m(m+1))\hat{y}_m\\
    &= \frac{d^2\hat{y}_m}{dx^2} + \frac{d\hat{y}_m}{dx}mx + m\frac{d\hat{y}_m}{dx}x + m\hat{y}_m + m\hat{y}_m x^2(m+2)(1-x^2)^{-1} \\
    &-2(m+1)x\left[  \frac{d\hat{y}_m}{dx} + \hat{y}_mm(1-x^2)^{-1}x \right] + (n(n+1)-m(m+1))\hat{y}_m\\
    \end{align*}
    and collecting some terms
    \begin{equation*}
    (1-x^2)\frac{d^2\hat{y}_m}{dx^2} - 2x\frac{d\hat{y}_m}{dx} + \left( -x^2 \frac{m^2}{1-x^2} + m+n(n+1)-m(m+1)\right)\hat{y}_m=0.
    \end{equation*}
    Showing that 
    \begin{align*}
    -x^2 \frac{m^2}{1-x^2} + m+n(n+1)-m(m+1) &= n(n+1)- m^2 -x^2 \frac{m^2}{1-x^2} \\
    &= n(n+1)- \frac{m}{1-x^2}
    \end{align*}
    implies $\hat{y}_m(x)$ being a solution of Eq.\eqref{kugel:eq:associated_leg_eq}
\end{proof}

\subsection{Orthogonality}